PELAKSANAAN PROGRAM VAKSINASI CORONA VIRUS DISEASE (COVID-19) PADA LANJUT USIA : STUDI KUALITATIF DI RUMAH SAKIT KELET KABUPATEN JEPARA - Dewi Puspitosari Hadi Saputro; Chriswardani Suryawati; Martini Martini (STIKES Cendekia Utama Kudus, 2023)
Based on the Instruction of the Minister of Home Affairs Number 24 of 2022 concerning the implementation of restrictions on community activities at level 3, level 2 and level 1 of the Corona Virus Disease 2019 in the Java and Bali Region according to the current level of the pandemic situation, Jepara district is placed in the PPKM level 2 position. Based on the evaluation results by the Office Health of Central Java Province in 2021, there are several problems that are likely to affect the success of the implementation of vaccinations in Jepara Regency in general and at Kelet Jepara Hospital in particular, including access for the elderly to get vaccines is still lowin Jepara Regency. This study aims to describe the implementation of the Covid-19 vaccination program for the elderly at the Kelet Regional General Hospital in Central Java Province in order to increase the target coverage of the elderly. The research was conducted at Kelet Hospital from September to November 2022. This research is a qualitative research where the research data is analyzed descriptively. Data analysis techniques use narrative analysis and data triangulation. The main informants consisted of 10 stake holders at Kelet Hospital and 4 patients who had been vaccinated at the Kelet Hospital Covid-19 vaccination polyclinic. The results showed that based on process factors, Kelet Hospital experienced external coordination problems due to limited human resources. Most of Human Resources focus on vaccination services and coordinate with internal hospitals. Other process factors have gone well including planning in the implementation of the Covid-19 vaccination program, recording & reporting systems, supervision/monitoring, and cross-program and cross-sector cooperation.COVID-19 Vaccination, the elderly, human resources